Complete chloroplast genome sequence of Epimedium shuichengense S. Z. He (Berberidaceae), an endangered species endemic to China. Issue 2 (2nd April 2020) - Yan, Fulin; Li, Lilang; He, Shunzhi; Wei, Shenghua; Sun, Qingwen
Abstract: Epimedium shuichengense S. Z. He is a rare and endangered species endemic to Guizhou, China. In this study, the complete chloroplast (cp) genome of E. shuichengense was sequenced. The total cp genomes size was 157, 046 bp in length, with 38.8% of GC content, including four distinct regions: the large single-copy region (LSC, 88, 394 bp), small single-copy region (SSC, 17, 048 bp), and a pair of inverted repeat regions (IRs, each for 20, 820 bp). The whole cp genome of E. shuichengense encoded 130 unique genes, including 85 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Phylogenetic analysis with the previously reported cp genomes showed that all the samples of Epimedium are grouped into one group, which can be easily separated from out groups, and E. shuichengense with E. borealiguizhouense into a supported branch.